Energy Consumption Analysis in the Plastic Waste Recycling Process: A Case Study of Amazia Vision Enterprise Private Limited, Satara, India - Ghadge, Tanmay; Khare, Vrushti; Bhosale, Shailesh; Giri, Prashant A; Jadhav, Vikas (Journal of Sustainability and Environmental Management, 2022)
Every year, over 400 million MT of plastic are produced around the world, majority of which aren’t managed properly, leading to immeasurable damage to the environment. Only 14-18% as a global average of plastic waste is recycled with only few companies take part in the plastic recycling process. The main goal of the study was to analyse the energy demand and provide a feasible technical solution to conserve energy and reduce the plant's operating costs. A plastic waste recycling station, Amazia Vision Enterprise Private Limited, Satara, India, was purposively chosen to conduct an extensive evaluation of energy requirements. An energy analysis was performed on the process to determine the potential for energy savings and cost reductions. It also aims to reduce the amount of energy used at each stage of the process. Theoretical solutions to conserve energy, reduce waste generation, and thus lower operating costs have been proposed. According to the analysis and subsequent evaluation, the energy requirement can be reduced to 8% of the initial value. A technical solution for recycling of plastics has been proposed which can be implemented to test the feasibility interms of both technical and economical parameters. An energy conservation analysis of a plant has been presented in this paper which will provide a road-map to conserve ever increasing energy consumption and drive more investors in the plastic recycling sector for best plastic waste management practices.